2017
DOI: 10.1016/j.bioactmat.2017.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary focus on the mechanical and antibacterial activity of a PMMA-based bone cement loaded with gold nanoparticles

Abstract: In total knee arthroplasty (TKA) and total hip replacement (THR) the restoration of the normal joint function represents a fundamental feature. A prosthetic joint must be able to provide motions and to transmit functional loads.As reported in the literature, the stress distribution may be altered in bones after the implantation of a total joint prosthesis. Some scientific works have also correlated uncemented TKA to a progressive decrease of bone density below the tibial component. Antibiotic-loaded bone cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 24 publications
3
68
0
Order By: Relevance
“…For example, incorporation of Au nanoparticles in a poly(methyl) methacrylate (PMMA)‐based bone cement improves the mechanical properties of the polymeric matrix and reduces the formation of S. aureus biofilms. [ 226 ]…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…For example, incorporation of Au nanoparticles in a poly(methyl) methacrylate (PMMA)‐based bone cement improves the mechanical properties of the polymeric matrix and reduces the formation of S. aureus biofilms. [ 226 ]…”
Section: Metal‐based Nanocompoundsmentioning
confidence: 99%
“…Modification of PMMA cements with bioactive particles have been suggested to prevent infections [14,[30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…PMMA bone cement (Palacos, Heraeus, Wehrheim, Germany) was modified with bioactive glass or copper doped tricalcium phosphate particles. Particles were dispersed in the solid PMMA phase as previously described [32]. Briefly, bioactive particles were dispersed into the solid PMMA phase through ultrasonic dispersion.…”
Section: Modified Pmma-based Bone Cementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternative strategies to prevent or fight infections are based on adding silver or gold nanoparticles, known for their antibacterial activity, to the cement . In their recent work, Russo et al reported a bone cement containing preformed gold nanoparticles in the 10–20 nm range that improved the antibacterial activity of the cement . With the goal of generating further improvements to the traditional use of preformed nanoparticles, the in situ generation of silver nanoparticles has been recently investigated.…”
Section: Chemical Phenomenamentioning
confidence: 99%